PENGEMBANGAN INSTRUMEN DIAGNOSIS KESEHATAN PENGANGGARAN SEKOLAH - Novia Sartika Putri, - (2020)
The research was titled "The Development of School Budgeting Health Diagnosis Instruments". In general, this study aims to produce an instrument to diagnose the health of school budgeting and to describe the health condition of school budgeting in public and private junior high schools (SMP) throughout Purwakarta Regency. The method in this research is descriptive with a quantitative approach. The sampling technique used in this research is Probability Sampling through Proportionate Stratified Random Sampling. While the data collection technique was carried out by distributing instruments in a closed manner through the application or google form link to 106 schools throughout Purwakarta Regency. The population in this study included principals, teachers, and administrative staff. Testing of this instrument is done through the construct test stage with expert lecturers (Judgment Expert), validity testing, and reliability testing. Data analysis in this study used the calculation of the Weight Means Score (WMS) with the help of the WPS Excel Office program and SPSS version 20.0 for windows. The findings from the results of data processing, as a whole, have a value range of 70-84 which is in the Healthy category. however, the average A Accredited school obtained the highest score of 3.42 or equivalent to a value of 85.49 which is included in the Very Healthy category. Meanwhile, the average school accredited C obtained the lowest score, namely 3.04 or equivalent to a score of 75.99 which is included in the Healthy category. Based on the results of this study, the health of school budgeting in Public and Private Junior High Schools (SMP) throughout Purwakarta Regency is healthy (free from organizational disease).